Research on privacy-preserving learning machines - Yi-zhang JIANG; Shi-tong WANG (网络与信息安全学报)
With the increasing development of data mining,more and more data mining methods need to be carried out on the privacy data,which leads to the serious problem of privacy disclosure.Therefore,Study of privacy-preserving learning machines is becoming a key data mining topic.Current privacy-preserving learning machines were surveyed and analyzed,including their basic ideas and their learning models.